ANALISIS KARAKTERISTIK CAMPURAN ASPAL EMULSI DINGIN (CAED) DENGAN EPOXY SEBAGAI BAHAN TAMBAH - Wikarga, I Gde; Arya Thanaya, I Nyoman; Suweda, I Wayan (JURNAL SPEKTRAN, 2017)
One of asphalt mixture being developed is Cold Bituminous Emulsion Mixtures (CBEMs) that its performances need to be improved. Within this experiment it is done by adding epoxy . The objective of this study was to analyze the characteristic of CBEMs with and without epoxy . Epoxy variation was 1%, 3%, and 6% by weight of residual bitumen. The epoxy was mix with hardener in ratio 1:3, then mixed with bituminous emulsion. Epoxy was added into the Optimum Residual Bitumen Content (ORBC) of 7,5%. The aggregate was dampened with water first then mixed with emulsion that had been added with epoxy, then compacted. It was found that CBEMs added with 1% and 3% epoxy met the specifications, however CBEMs with 6% of epoxy did not, because the porosity was 17,83% (spec.5%-10%). The soaked stability of the mixture without and with epoxy 3% was 1177,02 kg and 1416,47 kg.  Addition of 3% epoxy increase soaked stability up to 20%. In stiffness, creep, and fatigue tests, CBEMs without epoxy compared by CBEMs with 3% of epoxy , respectively gave result: stiffness 1854 MPa: 959 MPa (-48,27%); strain at 10 6 loads repetition (Nf) was 78,09 µ?: 93,22 µ? (+19,38%); Nf at strain 100 µ? was 358.897 times: 539.585 times (+50,35%); creep slope was 23,752: 39,939 (sample was collapsed before 3600 loads repetition). However, epoxy caused the mix stiffer hence increase the porosity of the mixture to 20%. It is suggested to reduce the hardener content of the epoxy , to manitain workability and reduce porosity.  Keyword : CBEMs, epoxy, stiffness, fatigue, creep